Spesialisering eller samvirke? Om skulptur og arkitektur i gjenreisnings- og vekstårene etter andre verdenskrig - Aamold, Svein (Nordlit, 2015)
One of the characteristics of modernist art and architecture is the insistence on autonomy. What happens if the two media are combined? Will they activate new artistic values – or will their insistence on individual autonomy lead to a differentiation which negates any true dialogue bearing on their status as works of art? These questions are discussed with references to sculptures by Georg Kolbe, Antoine Pevsner, Barbara Hepworth, Jean Arp, Arnold Haukeland and Ramon Isern; and the architecture of Ludwig Mies van der Rohe, Walter Gropius and Erling Viksjø. Also central to these topics are the public debates between architects, sculptors and architectural historians in Europe and America during the first decades after the Second World War. The issues regarding a possible integration of sculpture and architecture were highly contested during these years of optimism and economic growth. For some, the idea of a union between the two media proved to be an ideal that was perhaps never fully accomplished. Many sculptors, however, wanted to create works intended for public spaces, whether in architectural urban settings or in landscapes. Among the architects, the opinions differed from a refusal to include any works of art as part of their buildings, to those who involved in collaborative projects with artists. Others maintained that a new spatial unity could be achieved based on joint efforts on equal terms between sculptors and architects.